2022
DOI: 10.3389/fneur.2022.785040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fufang Huangqi Decoction on the Gut Microbiota in Patients With Class I or II Myasthenia Gravis

Abstract: ObjectiveTo investigate the effect of Fufang Huangqi Decoction on the gut microbiota in patients with class I or II myasthenia gravis (MG) and to explore the correlation between gut microbiota and MG (registration number, ChiCTR2100048367; registration website, http://www.chictr.org.cn/listbycreater.aspx; NCBI: SRP338707).MethodsIn this study, microbial community composition and diversity analyses were carried out on fecal specimens from MG patients who did not take Fufang Huangqi Decoction (control group, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Chen et al showed that the administration of Fufang Huangqi Decoction in eight MG patients (Myasthenia Gravis Foundation of America classes I and II) reduced the abundance of Blautia and Bacteroides and increased the presence of Bifidobacterium and Lactobacillus. These changes alleviated the symptoms of MG patients [ 71 ]. Although TCM originally appeared as a mythological doctrine, recently it has growing acceptance in Europe and in other Western countries [ 86 ].…”
Section: Clinical and Therapeutics Implicationsmentioning
confidence: 99%
“…Chen et al showed that the administration of Fufang Huangqi Decoction in eight MG patients (Myasthenia Gravis Foundation of America classes I and II) reduced the abundance of Blautia and Bacteroides and increased the presence of Bifidobacterium and Lactobacillus. These changes alleviated the symptoms of MG patients [ 71 ]. Although TCM originally appeared as a mythological doctrine, recently it has growing acceptance in Europe and in other Western countries [ 86 ].…”
Section: Clinical and Therapeutics Implicationsmentioning
confidence: 99%
“… 23 The microbiota of MG patients who were administered fufang huangqi decoction and achieved remarkable alleviation of symptoms underwent alteration, with the abundance of Blautia and Bacteroides decreasing and Bifidobacterium , Lactobacillus , and Roseburia increasing. 24 The progression of the disease was benefitted by the administration of two probiotic strains of Bifidobacterium and Lactobacillus in the Lewis rat model of myasthenia gravis (EAMG). Probiotic interactions with Peyer’s patches and greater α and β diversity in probiotic-treated EAMG were observed.…”
Section: Gut Microbiota and Myogenic Muscle Atrophymentioning
confidence: 99%
“… 28 Only one clinical intervention has demonstrated efficacy compared with no treatment; patients with MG administered fufang guangqi decoction achieve significant symptom relief. 24 Patients with MG who are medicated have different microbial communities than control patients; they tend to have lower levels of Blautia and Bacteroides and higher levels of Bifidobacterium and Lactobacillus at the genus level. 24 …”
Section: Gut Microbiota and Myogenic Muscle Atrophymentioning
confidence: 99%
“…Myasthenia gravis (MG) is an autoimmune disease caused by pathogenic autoantibodies targeting the neuromuscular junction (NMJ); these include anti-acetylcholinereceptor (AchR), anti–muscle-specific tyrosine kinase (MuSK), and anti–low-density lipoprotein receptorrelated protein 4 (LRP4) antibodies. Anti-AChR antibodyis detected with routine assays in 70–80% of all patients with MG. Based on the location of the affected muscles, MG is classified as ocular or generalized ( 3 ). The pathogenesis of MG is complex and involves an imbalance of gut microbiota ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%